2020
DOI: 10.1002/pon.5351
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and information needs of cancer patients regarding treatment‐focused genomic testing: A systematic review

Abstract: Objective: To systematically review literature exploring experiences of cancer patients regarding their understanding of treatment-focused genomic testing as well as their information needs and related themes.Methods: Six databases were searched for the original studies published in English language that explored patients' understanding of the information related to the genomic testing and its implications for treatment of cancer. The Mixed-Method Assessement Tool was used to examine the methodological quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 45 publications
(175 reference statements)
1
20
1
Order By: Relevance
“…CUP patients had poor understanding of the technical details of genomic testing, which is consistent with several studies in other cancer types 14 . However, most CUP patients had good understanding of the clinical implications of genomic testing, which was the more important for them.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…CUP patients had poor understanding of the technical details of genomic testing, which is consistent with several studies in other cancer types 14 . However, most CUP patients had good understanding of the clinical implications of genomic testing, which was the more important for them.…”
Section: Discussionsupporting
confidence: 82%
“…However, most CUP patients had good understanding of the clinical implications of genomic testing, which was the more important for them. This finding contrasts with a systematic review that indicated only 20%–38% of cancer patients were aware of genomic testing's link with identifying targeted treatment 14 …”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Alternatively, the information behaviour of interest can be further limited, e.g. information behaviour regarding the use of complementary and alternative medicine (Stub et al, 2020) or information needs regarding treatment-focussed genomic testing (Wolyniec et al, 2020). However, since the review by Rutten et al (2005), no reviews have focussed on reviewing the studies specifically addressing the use of information seeking by cancer patients as coping.…”
Section: Introductionmentioning
confidence: 99%
“…Over one-third of patients require additional counseling [14]. The review of Wolyniec et al [17]-analyzing quantitative and qualitative studies on knowledge and information regarding genomic testing-found that in some studies, less than half of patients were able to reflect the procedure and contents of molecular genetic testing. Considering their high expectations, especially regarding a potential treatment benefit [12][13][14]18], patients might have difficulties dealing with disappointments.…”
Section: Introductionmentioning
confidence: 99%